Bowaryzm – nuda – melancholia. Uwagi o bohaterach XIX-wiecznej literatury rosyjskiej - Kotkiewicz, Aurelia (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2019)
The article examines the notion of bovarism which can be seen in the work of the most outstanding Russian writers of the second half of the 19th century, for example Leo Tolstoy, Fyodor Dostoyevsky and Anton Chekhov. It seems that the source of bovaristic attitude, which is culturally, socially and psychologically motivated, is the extremity of the Russian character prone to self-sacrifice, offering and suffering, as well as cruelty and sadism. A Russian variant of bovarism is boredom and melancholy.